Global terrorism [electronic resource] - Lutz, James M.; Lutz, Brenda J. , 1957- (Routledge, 2008)
The new edition of this book continues to provide students with a comprehensive introduction to terrorism as a global phenomenon, introducing them to history, politics, ideologies and strategies of both contemporary and older terrorist groups.